KRIYA DAN DESAIN MENUJU PERKEMBANGAN KEKRIYAAN INDONESIA - Zainul Arifin MA (Jurnal DISPROTEK, 2016)
ABSTRACT Kriya in the context of the past is defined as an art product that contained the charge aesthetic value, symbolic, philosophical, and functional. The craft in the present context has a different understanding of that; can produce functional products and can produce art that is an expression of the individual for the sake of artistic prestige. Kriya have common terms and have many of the terms derivatives namely: Craft Art, Craft expression, Craft Design, Craft Design, Craft Product, and Contemporary Craft. These terms are essentially can be classified into two categories: the craft of design and craft art. The basic differences between the two categories lies in the motivation in the creation of its products. Kekriyaan activities should be conducted in order to craft an overall understanding, concerning the categorization in the craft, it became clear, that the "map" kriya can be read and understood. Including how to position the craft and skill collaborate with the design, resulting in an interesting craft products, functional, symbolic, aesthetic, quality and character. Keywords: craft, repositioning, collaboration and design ABSTRAK Kriya dalam konteks masa lampau dimaknai sebagai suatu produk seni yang terkandung muatan nilai estetik, simbolik, filosofis, dan fungsional. Adapun kriya dalam konteks masa kini memiliki pengertian yang berbeda yakni; dapat menghasilkan produk fungsional dan dapat menghasilkan produk seni yang merupakan ekspresi individual untuk kepentingan prestise kesenimanan. Kriya mempunyai istilah yang umum dan memiliki banyak istilah turunan yakni: Kriya Seni, Kriya Ekspresi, Disain Kriya, Kriya Disain, Kriya Produk, dan Kriya Kontemporer. Istilah-istilah tersebut pada hakikatnya dapat dikelompokan kedalam dua kategori yaitu kriya desain dan kriya seni. Perbedaan mendasar dari kedua kategori ini terletak pada motivasi dalam penciptaan produknya. Kegiatan kekriyaan harus sering dilakukan agar pemahaman kriya secara keseluruhan, menyangkut kategorisasi dalam kriya, menjadi jelas, sehingga ??peta? kriya dapat terbaca dan dapat dipahami. Termasuk bagaimana memposisikan kriya dan mengkolaborasikan kriya dengan desain, sehingga menghasilkan produk kriya yang menarik, fungsional, simbolis, estetis, berkualitas dan berkarakter. Kata kunci: kriya, reposisi, kolaborasi dan desain